Can social norm interventions promote voluntary pro environmental action?. Issue 89 (November 2018) - Huber, Robert A.; Anderson, Brilé; Bernauer, Thomas
Highlights: Substantial share of car owners willing to offset carbon emissions despite high costs. Government-led norm interventions can promote voluntary carbon offsetting behaviour. Peer group social norm interventions have little effect if behaviour is not yet widespread. Combination of both interventions perform best. Abstract: Conventional wisdom holds that voluntary pro-environmental action of citizens is desirable, but there remains much debate over how it could be promoted. We study this issue focusing on social norm interventions to increase voluntary carbon offsetting, which involves high personal costs. Specifically, we examine the causal effects of two types of social norm signals. One relates to attitudes and behaviour of other car owners (group information), the other to government policy on carbon offsetting, which carries an institutional signal of social desirability. While the former should have a positive effect, the latter could encourage or crowd out voluntary offsetting. Based on an experimental study design and a representative sample of 1919 car owners from the largest canton in Switzerland we find that, despite high costs, around 25% of our sample expressed a willingness to offset, and 11% actually paid to offset their emissions. The group norm intervention per se had little effect, but the combination of institutional and group norm signal caused a substantial increase in offsetting payment. Our study contributes to the discussion on how social norms and pro-environmental behaviour relate. The two main policy implications are that: (1) there is substantial room for using voluntary carbon offsetting to reduce emissions; and (2) institutional norm signals can promote voluntary carbon offsetting when pro-environmental behaviour is not yet widespread and group related norm interventions are thus difficult.